2014
DOI: 10.20885/jsb.vol18.iss2.art9
|View full text |Cite
|
Sign up to set email alerts
|

Determinan-determinan manajemen laba pada penawaran saham perdana (kasus pada perusahaan sektor aneka industri)

Abstract: This study analyzes the effect of operating cash flow, earnings changes, leverage, and the intended use of the IPO proceeds on earnings management of companies in various industry sector making initial public offerings (IPOs) in Indonesian stock exchange. The samples of this study were selected using purposive sampling method in which there were 15 out of 33 companies in the period 1990-2012. The data used are secondary data from a variety of industry sectors. The company's prospectuses are obtained from the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
0
0
3
Order By: Relevance
“…This result is consistent with results of study conducted by Zeller and Stanko (2000), Yoon and Miller (2002), Tresnaningsih (2008), Hughes et al (2010), Banimadh and Aliabadi (2013), Masoumi et al (2014), Gumanti et al (2014), Sibarani et al (2013), Andreas (2017),and Jang and Kim (2017). They found that operating cash flow had a negative effect on earnings management, which means that the lower the operating cash flow in a firm, the higher the tendency for the management of the firm to commit discretionary accruals by overstating earnings, and vice versa.…”
Section: The Influence Of Operating Cash Flow On Earnings Managementsupporting
confidence: 92%
“…This result is consistent with results of study conducted by Zeller and Stanko (2000), Yoon and Miller (2002), Tresnaningsih (2008), Hughes et al (2010), Banimadh and Aliabadi (2013), Masoumi et al (2014), Gumanti et al (2014), Sibarani et al (2013), Andreas (2017),and Jang and Kim (2017). They found that operating cash flow had a negative effect on earnings management, which means that the lower the operating cash flow in a firm, the higher the tendency for the management of the firm to commit discretionary accruals by overstating earnings, and vice versa.…”
Section: The Influence Of Operating Cash Flow On Earnings Managementsupporting
confidence: 92%
“…Hanya arus kas operasi yang berpengaruh negatif dan signifikan terhadap manajemen laba. (Gumanti et al, 2014). Arus kas operasi berdampak negatif terhadap manajemen laba (Marsela et al, 2016).…”
Section: Hubungan Manajemen Laba Dengan Kinerja Operasiunclassified
“…Temuan ini menyiratkan bahwa arus kas operasi berpengaruh negatif terhadap manajemen laba. Hal ini konsisten dengan hasil penelitian Trenaningsih (2008), Yanuar et al (2008), Hughes et al (2010), Bahnimadh dan Aliabadi (2013), Masoumi et al (2014), Gumanti et al (2014), Sibarani et al (2016), dan Andreas (2017) yang menjunjukkan bahwa adanya hubungan yang negatif antara arus kas operasi dengan discretionary accrual (manajemen laba). Hal ini bermakna bahwa semakin rendah arus kas operasi maka semakin kuat kecenderungan melakukan manajemen laba dan sebaliknya.…”
Section: Pendahuluanunclassified
“…Hasil penelitian Hughes et al (2010) menunjukkan bahwa arus kas operasi yang rendah dicurigai melakukan manajemen laba. Hal ini sejalan dengan hasil penelitian Zeller dan Stanko, 2000;Yoon dan Miller, 2002;Yanuar et al, 2008;Tresnaningsih, 2008;Hughes et al, 2010;Banimadh dan Aliabadi, 2013;Masoumi et al, 2014;Gumanti et al, 2014;Sibarani et al, 2013;Andreas, 2017; dan Jang dan Kim, 2017, yang menunjukkan bahwa arus kas operasi memiliki pengaruh negatif terhadap manajemen laba yang artinya semakin kecil arus kas operasi yang dimiliki perusahaan maka semakin besar peluang manajemen perusahaan melakukan tindakan manajemen laba yang menaikkan laba, dan sebaliknya. H2: Arus kas operasi berpengaruh terhadap manajemen laba.…”
Section: Pengaruh Arus Kas Bebas Terhadap Manajemen Labaunclassified